"The 1619 Project" and Social Work Curriculum: Preparing Students for Anti-Racist Micro- and Macro-Practice. - Moore, Sharon E.; Sterrett-Hong, Emma M.; Srivastava, Ankur; Crosby, Shantel; Kendrick, Jennifer; Miller, Shawnise Martin; Collins-Camargo, Crystal; Garcia, Rudy; Jenkins, David (Journal of Social Work Education)
"The 1619 Project," developed by journalist Nikole Hannah-Jones for the New York Times Magazine, examines ways the abolished institution of slavery is implicated in contemporary racial inequities in the U.S., as well as the accomplishments of Black Americans despite layered structural oppression. A school of social work at a Research I university deemed "The 1619 Project" an apt pedagogical tool for preparing social work students, across undergraduate and graduate programs, to address anti-Black racism at micro- and macro-levels. In this paper, the authors use Critical Race Pedagogy principles as a theoretical underpinning and present various coordinated learning activities utilizing "The 1619 Project" to elucidate manifestations of systemic racism. The paper concludes with implications for social work practice and education.